2014
DOI: 10.1080/00103624.2014.883627
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pistachio Trees with Zinc and Copper in Time of Swollen Bud in Two Consecutive Years

Abstract: This study was done to investigate the effects of foliar sprays of zinc (Zn) and copper (Cu) on fruit set, yield, yield components, vegetative growth, and leaf nutrient concentrations of pistachio trees (cv. Owhadi), over two consecutive seasons 2010 (ON) and 2011 (OFF). Tests were done at a commercial orchard in the region of Rafsanjan in Iran. Tests were designed as a 3 × 2 factorial experiment in a randomized complete block with four replications. Treatments tested in the study were three concentration leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Therefore, the PBTS1 and PBTS2 chromosomes were mined for the presence of genes putatively involved in bactericide resistance and antimicrobial production. To mitigate copper micronutrient deficiencies in pistachio orchards, trees are fertigated or sprayed with copper sulfate (Kallsen et al, 2000;Soliemanzadeh et al, 2014). Additionally, copper fungicides are used for the management of Septoria leaf spot (Michailides, 2005).…”
Section: Complementary Activities In Pbts2 Might Support Habitat Fitnmentioning
confidence: 99%
“…Therefore, the PBTS1 and PBTS2 chromosomes were mined for the presence of genes putatively involved in bactericide resistance and antimicrobial production. To mitigate copper micronutrient deficiencies in pistachio orchards, trees are fertigated or sprayed with copper sulfate (Kallsen et al, 2000;Soliemanzadeh et al, 2014). Additionally, copper fungicides are used for the management of Septoria leaf spot (Michailides, 2005).…”
Section: Complementary Activities In Pbts2 Might Support Habitat Fitnmentioning
confidence: 99%
“…It was revealed that foliar application of zinc sulfate (1 and 2 g L-1) increased yield of pistachio (Kizilgoz et al 2010). Also Soliemanzadeh et al (2014) reported that the foliar application of zinc and copper on pistachio trees at high levels, significantly increased primary and final fruit set, yield and yield quality when compared with control. Kizilgoz, et al,(2010) investigate that an increased fruit yield of pistachio trees from zinc application as a result of increased leaves zinc content.…”
Section: -Yield Per Shoot (G)mentioning
confidence: 97%